2009
DOI: 10.1037/a0014079
|View full text |Cite
|
Sign up to set email alerts
|

Norms for change in episodic memory as a prerequisite for the diagnosis of mild cognitive impairment (MCI).

Abstract: The new diagnostic criteria for mild cognitive impairment (MCI) from the International Working Group on Mild Cognitive Impairment (Winblad et al., 2004, p. 243) list "evidence of decline over time in objective cognitive tasks" as one diagnostic sign, implying the repeated neuropsychological testing. This study aimed to compare different assessment methods of longitudinal change based on the performances of 366 cognitively healthy participants (237 men, 129 women) examined with a German version of the Californi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 53 publications
1
21
0
3
Order By: Relevance
“…This kind of effect has been extensively documented in healthy participants for tasks assessing different cognitive functions including verbal episodic memory 38. Contrary to some studies,37 39 the observed improvement was not limited to the second testing but was observed during the entire study (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…This kind of effect has been extensively documented in healthy participants for tasks assessing different cognitive functions including verbal episodic memory 38. Contrary to some studies,37 39 the observed improvement was not limited to the second testing but was observed during the entire study (data not shown).…”
Section: Discussionmentioning
confidence: 46%
“…First, these results only inform us about change in patients with amnestic MCI, as we did not have other groups (e.g., cognitively intact, Alzheimer’s disease). Prior studies have examined these other phases along the continuum of late-life cognition (Bläsi et al, 2009; Duff et al, 2012; Gavett, Ashendorf, & Gurnani, 2015), and the current results would not necessarily generalize to those other groups. Our comparison sample from Duff (2014) was composed of subjects classified as cognitively intact and amnestic MCI.…”
Section: Discussionmentioning
confidence: 85%
“…No obstante, la mejora del rendimiento de los participantes en la evaluación de seguimiento, en este caso llevada a cabo un año después, podría poner en cuestión, el uso repetido de pruebas de memoria episódica y aprendizaje de listas de palabras. Ello puede ser debido a la presencia de diferentes factores que pueden influir de forma favorable en dicho rendimiento: 1) el efecto de la práctica y el efecto del aprendizaje, es decir, los participantes podrían haber recordado los elementos de las listas de palabras y/o podrían haber rememorado las estrategias que les resultaron efectivas en la codificación y posterior recuerdo, aunque no recordasen los elementos específicos que componen la prueba (Benedet y Alejandre, 1998;Collie, Maruff, Darby y McStephen, 2003); 2) el efecto de la familiaridad del test, que supone que los participantes podrían haberse familiarizado con el procedimiento de la prueba y, de ese modo, enfrentarse a la prueba de una forma más tranquila ante la evaluación de seguimiento (Bläsi et al, 2009;Rabbitt, Lunn y Wong, 2008); y 3) el efecto del entrenamiento cognitivo, en el sentido de que la participación de los mayores en programas de entrenamiento cognitivo podría dar lugar a una mejora en el rendimiento en este tipo de pruebas (Belleville, 2008).…”
Section: Discussionunclassified
“…En cuanto a los DCL inestables presentaron un mejor rendimiento en su segunda evaluación respecto a la primera en casi todas las subpruebas del TAVEC; estos resultados podrían deberse a que los participantes clasificados inicialmente como DCL, revirtieron a un estado cognitivo normal en su segunda evaluación. En este sentido, se considera que esta inestabilidad cognitiva puede ser debida a falsos positivos, es decir, el cambio de categoría diagnóstica puede ser debido al estado anímico o a problemas personales, que enmascaran la verdadera etiología cognitiva, y que pudieran haber interferido en el rendimiento cognitivo del participante en la primera evaluación (Artero et al, 2006;Bläsi et al, 2009;Peraita et al, 2011). Se ha de destacar que en este trabajo, en contra de lo esperado, la inestabilidad diagnóstica del grupo con DCL ha seguido una trayectoria cognitiva hacia la normalidad en lugar de evolucionar hacia un deterioro mayor, y, por tanto, con riesgo superior para el desarrollo de una posible demencia, como se podría esperar.…”
Section: Discussionunclassified
See 1 more Smart Citation